Strengthening students’ ability to create content in tourism brand communication - Henni Gusfa; Riki Arswendi; S. Syaefuddin (Journal of Community Service and Empowerment, 2023)
Vocational high school of 60 Duri Kepa Jakarta has an advantage in developing tourism learning. This is essential in realizing national development priorities, namely tourism. Students' abilities are supported by technological developments and various social media applications to communicate tourism branding in the city of Jakarta. A number of tourist destinations in Jakarta are popular and some are not popular, this issue has sparked student communication creativity in communicating the branding of tourist destinations. Community service programs in partnership with neighboring countries provide new enthusiasm in digital content literacy and environmental communication. Training on communicating tourism destination branding requires out of the box ideas, so that people or travelers can accept the meaning of branding communicated by students about the situation of the destinations they visit. This training results in changes in students' ability to communicate branding of tourist destinations in the city of Jakarta which is based on sustainable tourism communication.